2022
DOI: 10.1111/nph.18293
|View full text |Cite
|
Sign up to set email alerts
|

MYC transcription factors coordinate tryptophan‐dependent defence responses and compromise seed yield in Arabidopsis

Abstract: Summary Robust plant immunity negatively affects other fitness traits, including growth and seed production. Jasmonate (JA) confers broad‐spectrum protection against plant consumers by stimulating the degradation of JASMONATE ZIM‐DOMAIN (JAZ) proteins, which in turn relieves repression on transcription factors (TFs) coincident with reduced growth and fecundity. The molecular mechanisms underlying JA‐mediated decreases in fitness remain largely unknown. To assess the contribution of MYC TFs to growth and repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 104 publications
(210 reference statements)
0
13
0
Order By: Relevance
“…Among the genetic controls already identified as key regulators of growth-defense balance, the MYC transcription factors (TFs) stand out as examples whose function is wellstudied and understood. MYC2, MYC3 and MYC4 are the main TFs involved with the activation of the JA signaling pathway, thus being positively associated with upregulation of defense responses, but negative regulators of growth (Major et al, 2017;Ortigosa et al, 2020;Guo et al, 2022). In this Research Topic, Wang et al examined several myc single and higher order mutants in A. thaliana to examine the individual roles of these TFs and found that, consistent with previous work, MYC3 had the strongest effect on insect resistance (Fernańdez-Calvo et al, 2011).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Among the genetic controls already identified as key regulators of growth-defense balance, the MYC transcription factors (TFs) stand out as examples whose function is wellstudied and understood. MYC2, MYC3 and MYC4 are the main TFs involved with the activation of the JA signaling pathway, thus being positively associated with upregulation of defense responses, but negative regulators of growth (Major et al, 2017;Ortigosa et al, 2020;Guo et al, 2022). In this Research Topic, Wang et al examined several myc single and higher order mutants in A. thaliana to examine the individual roles of these TFs and found that, consistent with previous work, MYC3 had the strongest effect on insect resistance (Fernańdez-Calvo et al, 2011).…”
mentioning
confidence: 71%
“…Among the genetic controls already identified as key regulators of growth-defense balance, the MYC transcription factors (TFs) stand out as examples whose function is well-studied and understood. MYC2, MYC3 and MYC4 are the main TFs involved with the activation of the JA signaling pathway, thus being positively associated with upregulation of defense responses, but negative regulators of growth ( Major et al., 2017 ; Ortigosa et al., 2020 ; Guo et al., 2022 ). In this Research Topic, Wang et al.…”
mentioning
confidence: 99%
“…In this study, numerous cis -acting elements were found in promoters, and they are closely associated with various abiotic stresses. The promoter region of PtTPX2 contained a large number of binding elements, which are also related to the stress response ( Major et al., 2017 ; Guo et al., 2022 ). The results of RT-qPCR showed that salt stress, heat stress and drought stress can significantly change the PtTPX2 gene in different tissues or treatment times.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of both tryptophan and GS biosynthesis pathways has been reported to be an integral part of JA mediated defenses in response to wounding, necrotrophic pathogens, herbivores, exogenous application of JA and constitutive JA signaling in a jazD mutant devoid of ten of the family members of the JAZ repressor proteins (57,(66)(67)(68)(69)(70). Introgression of a myc234 loss of function mutation into the jazD background abolished gene expression of biosynthetic pathways and accumulation of tryptophan and IGs (69) showing dependence on these transcription factors. In addition, the myc234 mutant is known to be compromised in both tryptophan and GS biosynthesis (57).…”
Section: Discussionmentioning
confidence: 99%